EVALUASI PROGRAM SATU MILYAR SATU KECAMATAN DI KECAMATAN RIMBO ULU KABUPATEN TEBO PROVINSI JAMBI TAHUN ANGGARAN 2014 - Risa Prastiani; Hendry Andry (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2017)
Proverty happened in society leads the society itself can not fullfil the daily needs. The proverty alleviation has been a major target of government. The regional autonomy also one of the reasons government iniating to arrange one or some programs for the sake of prosperity. This research aims to find out and measure to what extent the implementation of bedah rumah program of one billion one subdistrict in Rimbo Ulu of Tebo Regency of Jambi Province in 2014. This research is using program evaluation theory in which according to Wirawan, evaluation program is a a systematic method to collect, to analyzed, and to answer the basic question about a program. Program evaluation can be classified based on process evaluation i.e evaluating whether or not the implementation of a program has been suitable with the strategy or planning, outcome program which is used to evaluate whether or not the program has yielded changes, and impact program which is used to evaluate whether or not there is an effect emerged due to the program. The population of the research is the subdistrict head of Rimbo Ulu, the staff or Rimbo Ulu subdistrict, the heads of the villages in Rimbo Ulu, and the society or inhabitants as the receivers of “bedah rumah” program. The population then is taken as samples using census technique. The data collection is conducted by giving questionnaires, doing interview, documentation and observation, to identify the result of the program. After data collection is done, the data is analyzed using percentage technique to find out how the responses of the respondents which state optimum, optimum enough, or less optimum. Based on the analyzed, it is obtained the result and findings of the research, and is concluded that the “bedah rumah” Program Of One Billion One subdistrict Program Rimbo Ulu Of Tebo Regency Of Jambi Province In 2014, chategorized as “optimum enough”. This is based on the responses and statements of the research respondents.